2019
DOI: 10.1108/k-05-2018-0245
|View full text |Cite
|
Sign up to set email alerts
|

Export knowledge

Abstract: Purpose This paper aims to study the export knowledge to be the determinant of export strategy, export commitment and export performance in carpet Industry. Design/methodology/approach Using a qualitative–quantitative approach, the unit of analysis is the individual export venturing firm in India. More in detail, a qualitative analysis was conducted through a focus group interview to explore the challenges of carpet exports. A quantitative analysis was performed using confirmatory factor analysis (CFA) and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Export knowledge is the understanding gained from data, information, and experience that allows a firm to export goods and services to other markets [ 17 ]. Export knowledge is also one of the firm’s intangible resources [ 19 ].…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Export knowledge is the understanding gained from data, information, and experience that allows a firm to export goods and services to other markets [ 17 ]. Export knowledge is also one of the firm’s intangible resources [ 19 ].…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…The recent literature gives more attention to RBV as this theory focuses on internal resources for better firm performance. According to Di Fatta et al [ 17 ], export knowledge and capability have become increasingly critical factors in competing foreign markets. Cooper and Kleinschmidt [ 50 ] also confirmed that firms with higher export growth have in-depth customer knowledge than increasing sales volume.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations